2007
DOI: 10.1007/s11606-007-0332-z
|View full text |Cite
|
Sign up to set email alerts
|

Academic Physicians Use Placebos in Clinical Practice and Believe in the Mind–Body Connection

Abstract: Nearly half of the respondents use placebos in clinical practice and most believe in the mind-body connection. The results of this study, based on retrospective self-reported behavior, are subject to recall bias and may not be representative of American physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
130
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 8 publications
10
130
0
5
Order By: Relevance
“…However, it can be certainly concluded that there is high prevalence of placebo use in clinical practice. Consistent with previous studies, [2,5] this study also found that most of the doctors believed that the effect of placebo was attributable to a psychological mechanism. …”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, it can be certainly concluded that there is high prevalence of placebo use in clinical practice. Consistent with previous studies, [2,5] this study also found that most of the doctors believed that the effect of placebo was attributable to a psychological mechanism. …”
supporting
confidence: 91%
“…[4] Another study reported 60% prevalence, [2] a national survey of U.S. internists and rheumatologists showed 55% prevalence [3] while a study of U.S. academic physicians reported 45% prevalence. [5] Our study showed higher (89%) prevalence of placebo prescribing; and of these, 80% reported using it more than 10 times a year. With 27% of the GPs reporting daily use of placebo, this group seems to be the highest placebo user, possibly due to reasons like limited diagnostic skills, giving in to patients' demands, etc.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…Still, a recent study (Sherman and Hickner 2008) found 45% of doctors had given placebos in clinical practice, but only 4% told patients of the placebos. On one hand, it seems as if a large fraction of doctors may be violating the moral approach cited above.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In Chicago, 45% of 231 internists affiliated with three local medical schools admitted to using the placebo. [12] In another study in Israel, they questioned 90 physicians and nurses in primary and tertiary care and found that 60% used the placebo. [13] Hemodialysis nurses develop a close relationship with patients as dialysis treatment is typically required three days a week and they mostly know about the patients' physical situations.…”
Section: Introductionmentioning
confidence: 99%